Digitizing Information in Islamic Boarding Schools: Efforts to Enhance Transparency and Accountability in Governance - Rahmat Fauzi; Ibnu Elmi A.S Pelu; Ajeng Hijriatul Aulia (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
This study aims to analyze the practice of information digitization in the governance of Islamic boarding schools based on the principles of Good Governance. A descriptive qualitative approach with field-based case study methods was employed. Data were collected through literature review—drawing on accredited national journals, academic books, research reports, legal regulations, and relevant scientific articles—and through direct observation and documentation of digital practices in several Islamic boarding schools in the Kalimantan and Java regions. The analysis focused on themes such as the role of kiai in institutional management, the Islamic boarding school education system, the digital transformation of religious institutions, and the implementation of sound governance principles from an Islamic perspective. The findings reveal that several pesantren have adopted digital management applications, institutional social media platforms, and integrated financial and administrative reporting systems. These digital transformations have enhanced institutional transparency, managerial efficiency, and public accountability. The study concludes that information digitization is a strategic tool for establishing modern and accountable Islamic school governance. The implications highlight the need for improved digital infrastructure, increased technological literacy among pesantren stakeholders, and integrating Islamic values into technology-based governance to ensure sustainable institutional transformation.